Pharmacological evaluation of SN79, a sigma (σ) receptor ligand, against methamphetamine-induced neurotoxicity in vivo - Kaushal, Nidhi (2012)
Methamphetamine is a highly addictive psychostimulant drug of abuse, causing hyperthermia and neurotoxicity at high doses. Currently, there is no clinically proven pharmacotherapy to treat these effects of methamphetamine, necessitating identification of potential novel therapeutic targets. Earlier studies showed that methamphetamine binds to sigma (σ) receptors in the brain at physiologically relevant concentrations, where it acts in part as an agonist. SN79 (6-acetyl-3-(4-(4-(4-florophenyl)piperazin-1-yl)butyl)benzo[d]oxazol-2(3H)-one) was synthesized as a putative σ receptor antagonist with nanomolar affinity and selectivity for σ receptors over 57 other binding sites. SN79 pretreatment afforded protection against methamphetamine-induced hyperthermia and striatal dopaminergic and serotonergic neurotoxicity in male, Swiss Webster mice (measured as depletions in striatal dopamine and serotonin levels, and reductions in striatal dopamine and serotonin transporter expression levels). In contrast, di-o-tolylguanidine (DTG), a well established σ receptor agonist, increased the lethal effects of methamphetamine, although it did not further exacerbate methamphetamine-induced hyperthermia. Together, the data implicate σ receptors in the direct modulation of some effects of methamphetamine such as lethality, while having a modulatory role which can mitigate other methamphetamine-induced effects such as hyperthermia and neurotoxicity.